Modelo de governança para garantir a qualidade de serviço em redes com SLA - SOUZA, Antônio Henrique P. de (2017)
Currently in the globalized and competitive market, where several challenges and constant changes take place, it is necessary to promote the development and strategic use of creative and effective governance models capable of meeting and satisfying all the needs of consumers in the most varied segments of the economy. Thus, this dissertation has as general objective to present a proposal of a governance model to guarantee the quality of service - QoS in contracts with SLA (Service Level Agreement) in Internet access providers. A model of Governance based on the objectives, benefits, applicability of the COBIT, ITIL and ISO / IEC 20000 models have been proposed. They have been related to the best practices of these models with regard to the quality of services in network environments that require SLA, aiming at fixing Problems related to network outage, network latency variation, and transfer rates that go into disagreement with contracts entered into between clients and providers. For this work to be completed, bibliographic research, descriptive and exploratory research were used, and qualitative and quantitative approaches were taken in a field study, which included the application of a questionnaire with open questions to the manager and network analysts of a company and questionnaires with questions to customers. The model incorporates features inherent to the consolidated models of COBIT, ITIL and ISO / IEC 20000 and established differential aspects, with a view on improving solutions to the problems diagnosed in the provision of Internet access services based on SLA contracts, reflecting quantitative gains in the various processes of interaction between the service provider and its respective contractors. The model provided a quality gain in SLA network deployments, ensuring greater customer satisfaction.